Accuracy assessment of bolus and basal rate delivery of different insulin pump systems used in insulin pump therapy of children and adolescents. Issue 4 (7th February 2020) - Ziegler, Ralph; Waldenmaier, Delia; Kamecke, Ulrike; Mende, Jochen; Haug, Cornelia; Freckmann, Guido
Abstract: Background: Continuous subcutaneous insulin infusion (CSII) is commonly used in patients with diabetes. Accurate and reliable delivery by insulin pumps is essential for a safe and effective therapy, particularly when using small doses. In this study, accuracy of bolus and basal rate delivery of various available insulin pumps was evaluated. Methods: In total, 13 insulin pump systems were tested: eight durable pumps with different infusion sets and one patch pump. Based on IEC 60601‐2‐24, insulin delivery was measured by recording weight gain of a beaker into which insulin was infused by the pumps. Bolus accuracy was determined by individually weighing 25 consecutive 0.1 or 1.0 U boluses and basal rate accuracy was determined during basal rate delivery of 0.1 or 1.0 U/h for 72 hours. For analyses, basal rate delivery was divided into 1‐hour windows and deviation from target was calculated. Results: Regarding different systems, average 0.1 U bolus delivery was −2% to +9% of the intended volume with 53% to 96% of boluses within ±15% of target. During 0.1 U/h basal rate delivery, most pumps showed an initial over‐delivery for the first few hours. Three systems reached a total basal rate error <5%; others showed up to +24%. In general, delivery was more accurate when using larger doses. Conclusions: Considerable differences in insulin delivery accuracy were observed between the tested pumps. In general, when using very low doses, accuracy of insulin delivery is limited in most insulin pumps. This should be considered for CSII therapy in children.